GENDER ASPECTS IN ENGLISH MEN’S CONGRATULATORY SPEECHES - Ernazarova Nargiza Xidirovna (TARJIMASHUNOSLIK VA TILSHUNOSLIKNING DOLZARB MUAMMOLARI: ZAMONAVIY TENDENSIYALAR VA YONDASHUVLAR, 2025)
This study examines how English-speaking men construct masculinity through congratulatory discourse, particularly in birthday greetings to their wives. It analyzes lexical, stylistic, and pragmatic features to reveal emotional expressiveness and partnership. Using discourse and gender theories, the research shows that modern masculine speech reflects empathy and equality, shifting from patriarchal norms toward emotional reciprocity and appreciation.